The effect of "what's another way method" on creativity ability in problem solving - Hanik Lestari; Ali Mustadi (Jurnal Pendidikan dan Pengajaran, 2019)
Creativity is one of the necessary skills in problem solving. One method in problem problem is What other way. The study was conducted to find out information about other way about the ability and problems in the students in the field of Advanced Mathematics Education of integer material. The study involved 76 students from University in Yogyakarta. This research method is quasi experiment. Instrument of creativity problem solving of pre test and post test conducted in experiment class and control class. The results of that test include creativity in the problem that includes three indicators, fluency,  flexibility, and novelty. Then, the data were analyzed by comparing the results of pre test and post test in the control and experimental class. Data analysis is also reinforced by gain score. The results of this study is  being the response of students towards learning by using the "what's another way" is positive